Recommendations for the optimization of student led free vision screening programs - Nirupama Devanathan; Melanie Scheive; Amrish Selvam; Baraa S. Nawash; Alec Murphy; McKenna Morrow; Shruti Anant; Jessica S. Kruger; Chi-Wah Rudy Yung; Thomas V. Johnson (BMC Medical Education)
Abstract Purpose To report the summary characteristics of operational models associated with Student Led Free Vision Screening Programs (SLFVSP) and to identify opportunities for program optimization. Methods An 81-question mixed methods survey was distributed to SLFVSP leaders nationwide and Medical Student Educators within the American University Ophthalmology Professors (AUPO) Association. Survey responses were analyzed using Mann Whitney U and Fisher’s Exact tests. Themes considering the assets and liabilities of SLFVSPs were summarized using self-reported qualitative data from survey responses. Qualitative and quantitative themes considering were then synthesized into a Strengths, Weaknesses, Opportunities, & Threats (SWOT) analysis for a collective appraisal of SLFVSP operations. Finally, drivers were identified to generate change ideas to improve SLFVP operations through a collaborative, quality improvement model. Results A total of 16 survey responses were included from programs operational for a median of 6 years. Most respondent programs (n = 9) reported year-long operations; no preference between weekday (n = 8) and weekend (n = 7) screening activities was identified. Programs obtained funding from a diverse array of internal and external sources. There was no significant difference in wait time for scheduled appointments compared to a walk-in strategy; overall door-to-door visit times ranged from 15 min to 120 min. Screenings were held in several locations, most commonly in Federally Qualified Health Centers (n = 8) and religious centers (n = 6). Most screening event volunteers were first- and second-year medical students. The qualitative thematic analysis demonstrated that the most commonly self-reported asset was improving access to scarce vision screening services (n = 7) while the most commonly self-reported liability was difficulty recruiting faculty and/or resident for oversight (n = 5). The SWOT analysis revealed while the participant SLFVSPs were bolstered by site experience, community and corporate partnerships for glasses and space to hold vision screening, and institutional support from academic ophthalmology departments, limitations included difficulty with recruitment, space limitations, and poor follow-up care infrastructure. Conclusion Collaborative standardization of SLFVSP operations can promote targeted staff training, organizational stewardship, and consensus building to ensure SLFVSP can offer sustainable vision screening programs that build vision equity at the community level.